Implementasi Metode Smart Dalam Sistem Pendukung Keputusan Untuk Pemilihan Produk Sunscreen Berdasarkan Tipe Kulit - Devinta Amalia; Firman Pratama (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2026)
High exposure to ultraviolet radiation in Indonesia increases the risk of skin problems, making the use of sunscreen tailored to skin types essential. Manual selection is often subjective and does not adequately consider relevant criteria. This study develops a web-based decision support system for sunscreen selection at Havya Medika Clinic using the SMART (Simple Multi Attribute Rating Technique) method to rank 50 product alternatives based on five criteria: SPF, texture, type, size, and price, with SPF assigned the highest weight. Skin type data were obtained through interviews with a dermatology expert, while product data were collected from the technical specifications of various brands. The results show that Facetology Triple Care Sunscreen Tinted SPF 50 PA++++ ranks highest for normal skin (88.33), SCORA Bright Me Up Sunscreen SPF 40 PA++++ for dry skin (85.00), and Labore Acne & Oil Correct Physical Sunscreen for sensitive skin (85.42). User Acceptance Testing (UAT) involving 15 respondents yielded a score of 526 out of 600 (average of 4.38), with a feasibility rate of 87.67%, indicating that the system is highly feasible. The system effectively provides objective and measurable recommendations based on users’ skin types.